Phenotypic and Molecular Detection of Methicillin Resistance in S. aureus - Maribel Castellano González; Armindo Perozo Mena; Rosana Vivas Vega (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2008)
Detecting methicillin resistance is complicated due to the heterogeneity of its phenotypic expression, making its detection difficult in the laboratory; this has led to the development of several techniques to increase its expression in vitro. Four techniques for detecting methicillin resistance were evaluated: the disk diffusion method with oxacillin (OX, 1 μg) and cephoxitin (FOX, 30 μg); the screening test, minimum inhibitory concentration (MIC) and detection of PBP2a, using the presence of mecA gen as a reference method; 286 strains of S. aureus, were processed. The sensibility (SEN), specificity (SPE), positive predictive value (PPV), negative predictive value (NPV) and efficiency (EFC) of each method were determined. A total of 50 oxacillin resistant, PBP2a positive (mecA positive) strains were obtained. Sensibility of the OX disk was 99.14%; and of the FOX disk was 100%. The SEN, PPV, NVP and EFC of the other methods were 100%. All the tests, except the OX disk diffusion method (99.14% of ESP), were 100% specific.